Phenomenology for actors : theatre-making and the question of being - Johnston, Daniel, (Lecturer) (Intellect Books, 2021)
This book explores how phenomenology - the study of how the world shows itself to conscious experience - can provide new insights into acting and theatre-making. It explores Being-in-the-world in everyday life with practical exercises for rehearsal and performance. 7 b/w illus.